2011
DOI: 10.1007/s10753-011-9359-8
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Taurine on Brain 8-hydroxydeoxyguanosine and 3-nitrotyrosine Levels in Endotoxemia

Abstract: Taurine is a sulfur-containing β-amino acid that is found in milimolar concentrations in most mammalian tissues and plasma. It was shown to have cytoprotective effects in many in vitro and in vivo studies and these actions are often attributed to an antioxidant mechanism. In this study, we aimed to investigate the effect of acute taurine administration on endotoxin-induced oxidative and nitrosative stress in brain. Fourty adult male guinea pigs were divided into four groups: control, taurine, endotoxemia, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 35 publications
0
6
0
1
Order By: Relevance
“…As the markers of oxidative stress, 3-NT and 8-OHdG were the oxidative damage products of proteins and DNA, respectively, that were “attacked” by ROS. , As shown in panels A and B of Figure , the contents of 3-NT and 8-OHdG in the PA-treated group were increased by 15.33% and 32.39% compared to the control groups, respectively. However, coincubation with different concentrations (10, 50, and 100 μM) of PCA and 500 μM AICAR (an AMPK activator) effectively reduced the levels of 3-NT and 8-OHdG, indicating that PCA could ameliorate PA-induced oxidative damages of HUVECs in a dose-dependent manner.…”
Section: Resultsmentioning
confidence: 94%
“…As the markers of oxidative stress, 3-NT and 8-OHdG were the oxidative damage products of proteins and DNA, respectively, that were “attacked” by ROS. , As shown in panels A and B of Figure , the contents of 3-NT and 8-OHdG in the PA-treated group were increased by 15.33% and 32.39% compared to the control groups, respectively. However, coincubation with different concentrations (10, 50, and 100 μM) of PCA and 500 μM AICAR (an AMPK activator) effectively reduced the levels of 3-NT and 8-OHdG, indicating that PCA could ameliorate PA-induced oxidative damages of HUVECs in a dose-dependent manner.…”
Section: Resultsmentioning
confidence: 94%
“…The results of multiple regression analysis further showed that the increased 3-NT expression was closely related to alveolar bone loss and apoptosis of periodontium cells. Increased nitrotyrosine formation has been proved to be associated with various tissue injuries in lipopolysaccharide- (LPS-) treated rats, such as aortic and brain damage [23, 24]. LPS from Porphyromonas gingivalis , one of the most important pathogenic bacteria of periodontitis, contributes to the destruction of periodontal tissues.…”
Section: Discussionmentioning
confidence: 99%
“…The protective mechanism appears to be restoration of normal glutathione levels, consistent with taurine's antioxidant properties. Conversely, Ozan, Turkozkan, Bircan, and Balabanli, () reported an “antioxidative stress” when guinea pigs were treated with 300 mg/kg (i.p. ), with higher levels of DNA damage and 3‐nitrotyrosine levels in whole brain homogenates.…”
Section: Insights From Animal Studies: What Is the Evidence For Neuromentioning
confidence: 99%